Formulation and Evaluation of Perindopril Erbumine Mouth Dissolving Film Using 32 Factorial Design (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: The aim was to develop and optimize fast dissolving film of Perindopril Erbumine (PDP) bytwo-factor, three-level factorial design as the two independent variables inclusive of X1 Hydroxypropylmethylcellulose (HPMC) and X2 propylene glycol (PG) has been decided on the idea of the initial studies doneearlier than the experimental design is being implemented. Materials and Methods: HPMC E5 LV and PGwere used respectively as a film former and a plasticizer, to increase the physicochemical properties of the films,organized by the solvent casting method. Result and Discussion: Structured or reaction variables included %drug release in 10 min (Y1), disintegration time (Y2), and refolding strength (Y3). Basic reaction diagrams weredrawn, statistical validity of polynomials was established to identify optimized method compositions. The filmshave undergone in vitro drug release studies which have confirmed 90.97–99.36% drug release within 10 min.Ex vivo studies of optimized formulation confirmed 86% permeation of the drug through the oral mucosa ofsheep within 15 min and no cellular necrosis was found for the duration of the histological study. The stability ofoptimized batch was found to be stable for 6 months under specified stability conditions. Conclusion: PDP mouthdissolving film was formulated evaluated by using 32 factorial design.